O serviço social e o debate sobre a categoria trabalho: mediações para análise do assistente social como trabalhador assalariado - Gois, Juliana Carla da Silva (2014)
This dissertation aims to demonstrate how the work category and their expressions are analyzed by the Social Service productions that are based on Marxian and Marxist perspective, more precisely the productions that seek to explain the condition of worker Social Worker and their insertion in the division of work. To achieve this goal we resorted to the literature, based on a historical-critical perspective, with the reference to Marx and Marxist theory. Initially it was essential to develop a reasoned predominantly in the works of Karl Marx, in particular to his seminal book The Capital and scholars to study the Marxist tradition. From the return to the fundamentals of Marx develops a critical analysis around the work category in its ontological sense; the double dimension of work in capitalist society - concrete work and abstract work - articulated the analysis of the commodity; the foundations of the division of labor under capitalism, emphasizing periods of cooperation, and large manufacturing industry, which highlights the emergence of new employees, and expressions of this division of labor in capitalist society, as productive labor, unproductive labor and collective work . Also explains the specific way-which assumes the division of labor in monopoly capitalism, as it emphasizes the period of scientific management, which intensified the split between manual and intellectual labor and the expansion of wage employment. Also demonstrated in the study and the wage expansion of the service sector and the expansion of social services, which demand the need of the wages of new employees to perform these services. Finally, it points to the debate on the controversial perspectives and analysis of the social worker as an employee in the division of labor, exposing themselves as categories concrete labor, abstract labor, productive labor, unproductive labor and collective work are explained in the inside productions Social Service, particularly in the works of Marilda Iamamoto and Sergio Lessa. We show the views of the authors according to their theoretical positions, making the counterpoint of these positions with the conception of Karl Marx on the categories investigated. From this point out the existence of different mediations for the study of social work as a profession and social worker as an employee, as well as the need to differentiate the proletarians of non salaried workers employed in the latter case including whether social workers.